2019
DOI: 10.1002/tox.22835
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects against cadmium chloride‐induced hippocampal neurotoxicity by inhibiting ER stress and GAAD 153 and activating sirtuin 1/AMPK/Akt

Abstract: This study investigated whether the apoptotic effect induced by cadmium chloride (CdCl2) in rat's hippocampi and neuroprotection afforded by resveratrol (RES) are mediated by modulation of ER stress and involve sirtuin 1 (SIRT1)/AMPK/Akt axis. Adult male Wistar rats were divided into four groups (n = 24/group) as control, control + RES (300 mg/kg), CdCl2 (5 mg/kg), and CdCl2 + RES. All treatments were conducted orally for 45 days. Also, cultured hippocampal cells were treated with CdCl2 in the presence or abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…This was evident from an attenuated induction of ER stress-sensitive genes (HSPA5, DDIT3) and reduced splicing of XBP-1 in thyrocytes co-treated with RSV and TM as compared to thyrocytes treated with ER stress-inducer TM alone. The observed attenuation of TM-induced ER stress by RSV in the non-transformed FRTL-5 cell line is in line with a large number of published studies reporting an inhibitory effect of RSV on ER stress in different cell lines and tissues [ 19 , 20 , 21 , 22 , 23 , 24 ]. Second, the strong impairment of expression of genes involved in thyroid hormone synthesis and some of their transcriptional regulators (TTF-1, PAX-8) in FRTL-5 thyrocytes exposed to TM-induced ER stress is attenuated, but not completely abolished by RSV.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This was evident from an attenuated induction of ER stress-sensitive genes (HSPA5, DDIT3) and reduced splicing of XBP-1 in thyrocytes co-treated with RSV and TM as compared to thyrocytes treated with ER stress-inducer TM alone. The observed attenuation of TM-induced ER stress by RSV in the non-transformed FRTL-5 cell line is in line with a large number of published studies reporting an inhibitory effect of RSV on ER stress in different cell lines and tissues [ 19 , 20 , 21 , 22 , 23 , 24 ]. Second, the strong impairment of expression of genes involved in thyroid hormone synthesis and some of their transcriptional regulators (TTF-1, PAX-8) in FRTL-5 thyrocytes exposed to TM-induced ER stress is attenuated, but not completely abolished by RSV.…”
Section: Discussionsupporting
confidence: 83%
“…Amongst these compounds, the polyphenol resveratrol (RSV; IUPAC name: 5-[(E)-2-(4-hydroxyphenyl)ethenyl] benzene-1,3-diol), which is naturally found at high concentrations in red grapes and different berries, like blueberries, mulberries and raspberries, is a potential candidate for the treatment of ER stress-associated thyroid disorders. RSV was shown to inhibit ER stress in different cell types and tissues [ 19 , 20 , 21 , 22 , 23 , 24 ] and to induce the expression of NIS and key regulators of genes involved in thyroid hormone synthesis, such as TTF-1, TTF-2 and PAX-8, in non-transformed FRTL-5 thyrocytes and thyroid carcinoma cells [ 25 , 26 ]. In view of this, the present study tested the hypothesis that RSV alleviates the inhibitory effect of TM-induced ER stress on expression of genes involved in thyroid hormone synthesis and their transcriptional regulators in FRTL-5 thyrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an ordered and orchestrated cellular process of programmed cell death that occurs in physiological and pathological conditions, and it plays an important role in the pathogenesis of many diseases such as degenerative neurological diseases. The apoptosis of the hippocampus can be induced by many chemicals such as bisphenol A (Lee et al, 2008), perfluorooctane sulfonate (Li et al, 2017), and cadmium (Shati, 2019). However, there is no study showing that DEHP can induce apoptosis of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports suggested that the SIRT family may be associated with the regulation of ER stress and cell apoptosis 28,29 . To clarify the role of SIRT proteins in NCTD combined with PTX in PCa cells.…”
Section: Resultsmentioning
confidence: 99%